1977
DOI: 10.1007/bf00288460
|View full text |Cite
|
Sign up to set email alerts
|

Synaptonemal complex karyotyping in spermatocytes of the Chinese hamster (Cricetulus griseus)

Abstract: The X and Y chromosome axes have a distinctive morphology at pachytene and are clearly distinguishable from autosomal SCs. The X and Y are totally unpaired at late zygotene when most of the autosomes are synapsed; however, their attachment points at the presumptive SC end are closely apposed. The X and Y axes pair to form a length of SC that is somewhat shorter than the unpaired portion of the Y. Unpaired axes may appear thin and sometimes double, or may thicken to form fusiform bulges that are sometimes hollo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
105
0
2

Year Published

1986
1986
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(123 citation statements)
references
References 19 publications
16
105
0
2
Order By: Relevance
“…This study recorded a 1 .8x range of SC lengths among pachytene oocytes and also concluded that SC lengths initially decreased during early to mid pachytene before extending again during late pachytene. A similar pattern of change in SC length was described in hamster spermatocytes, where sub-stages of pachytene Carmi et al (1978) were defined by changes in XY morphology (Moses et a!., 1977 (Gillies, 1983). The ranges of SC lengths observed in Crepis capillaris are similar to those described in maize which supports the contention that the pachytene nuclei analysed in the present study represent the entire range of pachytene.…”
Section: Introductionsupporting
confidence: 54%
“…This study recorded a 1 .8x range of SC lengths among pachytene oocytes and also concluded that SC lengths initially decreased during early to mid pachytene before extending again during late pachytene. A similar pattern of change in SC length was described in hamster spermatocytes, where sub-stages of pachytene Carmi et al (1978) were defined by changes in XY morphology (Moses et a!., 1977 (Gillies, 1983). The ranges of SC lengths observed in Crepis capillaris are similar to those described in maize which supports the contention that the pachytene nuclei analysed in the present study represent the entire range of pachytene.…”
Section: Introductionsupporting
confidence: 54%
“…The staining was monitored under phase contrast or conventional optics and, when the staining was considered appropriate, the coverslip was floated offand the slides washed in distilled water and dipped for 10 sec in 0.4% Kodak Photoflo 200 adjusted to pH 8.2 with borate buffer before air drying. Some spreads were stained with phosphotungstic acid (PTA) as described by MOSES (46). One part of aqueous 4% PTA was mixed with three parts of 96% ethanol and the slides were stained for 10 min in the mixture whereafter they were washed in 96% ethanol and air dried.…”
Section: Methodsmentioning
confidence: 99%
“…Despite this, its condensation is quite differentiated from that of the autosomal segments in Artibeus lituratus. According to SOLARI (1974), SHARP (1982) and MOSES (1977), species analyzed that have multiple systems and that present variations in the condensation of the sex axes, conserve these types of modification in taxonomic groups. Species of Macropus (marsupial) have intense condensation in the axes of the sex chromosomes similar to that of eutherians (MOSES 1977) with almost identical modifications.…”
Section: Dmentioning
confidence: 99%
“…According to SOLARI (1974), SHARP (1982) and MOSES (1977), species analyzed that have multiple systems and that present variations in the condensation of the sex axes, conserve these types of modification in taxonomic groups. Species of Macropus (marsupial) have intense condensation in the axes of the sex chromosomes similar to that of eutherians (MOSES 1977) with almost identical modifications. Perhaps due to the lack of a broader analysis of TUCKER and BICKHAM (1986), in Stenodermatinae bats, it was not possible to observe differentiation in the condensation of the original axes of X and Y.…”
Section: Dmentioning
confidence: 99%